Risk Management of Software Projects - Mohamed Abdullah Mahmoud (International Journal of Computers and Informatics, 2023)
Risk management has gained increasing importance in the field of software project management because of its direct impact on project success. Therefore, software organizations are challenged to achieve effective and efficient risk management. So, measuring risk in software development is a key activity to be done in risk management. Risk measurement is also an important topic that needs more effort, especially in a work environment with multiple software projects. A multi-project environment involves many projects sharing the same available resources. This research aims to conduct a literature review to discover patterns or trends in software development to measure project risk and to reveal aspects of the measurement process, risk indicators, and different metrics for software projects. This research also aims to present a proposed framework for assessing risks in a work environment with multiple projects with shared resources for different levels in organizations with different capabilities.
Keywords: Risk Management; Project Management; Software Development Projects; Risk Assessment